Radiation of charge passing by impedance wedge - Ostroushko, V. (Вопросы атомной науки и техники, 2021)
The diffraction radiation generated by a charge passing by a plasma wedge is considered in impedance approximation. In the perfect conductivity limit, the total radiated energy is not varying with the wedge rotation around the edge fixed along with the charge motion line. The impedance increase may lead to the total radiated energy increase, due to effective surface wave generation, when the charge motion to the edge is almost parallel to a face of wedge.